Meningkatkan Hasil Belajar Matematika Dengan Media Konkrit Kelas II SDN 6 Baturetno Kecamatan Baturetno Tahun Pelajaran 2019/2020 - Nursari, Beni (Universitas Sebelas Maret, 2020)
The purpose of this study is to find out a positive relationship between the use of concrete object media and mathematics learning outcomes for second grade students at SDN 6 Baturetno Baturetno District for the 2019/2020 school year and to find out the contribution of the use of concrete object media to mathematics learning outcomes. This research is a quantitative and qualitative research. The initial condition of the mathematics scores of students who scored above the KKM was only 23% or as many as 3 children out of 13 students. After the end of the first cycle, the student's score was above the KKM 77%, then the second cycle was obtained or 13 children scored above the KKM or 100%. The success indicator of this research is the average grade of 82.30, the percentage of students who are above the KKM is 100% of the 13 students. Based on the analysis and discussion of the research results, it can be concluded that there is a positive relationship between the use of concrete object media and mathematics learning outcomes